Satisficing and prior-free optimality in price competition: a theoretical and experimental analysis - Werner Güth; Maria Vittoria Levati; Matteo Ploner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
On a heterogeneous experimental oligopoly market, sellers choose a price, specify a set-valued prior-free conjecture about the others' behavior, and form their own profit-aspiration for each element of their conjecture. We formally define the concepts of satisficing and prior-free optimality and check if seller participants behave in accordance with them. We find that seller participants are satisficers, but fail to be prior-free optimal.
Keywords: C92; C72; D43; 330; Satisficing behavior; bounded rationality; triopoly; Oligopol; Preiswettbewerb; Beschränkte Rationalität; Theorie